Sintesis dan Uji FTIR Barium M-Hexaferrite dengan Doping Logam Mn - Aris Doyan; Khalilurrahman Khalilurrahman; Susilawati Susilawati (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
Has successed studied shyntesis Barium M-Hexaferrite (BaM) powder with doping Mn and tested using Fourier Transform Infrared (FTIR). Shyntesis has using coprecipitation method. This study intend to describe substitute Mn against crystal bounded of BaM process with x = 0; 0.2; 0.4; and 0.6. BaM powder with doping Mn is dried on themperature 80 0C and calcined on themperature 400; 600; and 800 0C for 4 hours. Barium M-Hexaferrite BaFe12-xMnxO19 doped by Mn characterized using FTIR. The result show that wave number between 450 until 690 cm-1 is metal bound (Fe-O) on BaM phase and range between 1000 until 1650 cm-1 showing characteristic of Ba-O bound.